2002
DOI: 10.1046/j.1469-0705.2002.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of central pelvic recurrent disease with transvaginal color Doppler ultrasound in women treated for gynecological malignancy

Abstract: Color Doppler analysis added to transvaginal gray-scale ultrasonography seems to be a helpful tool in the diagnosis of recurrent tumors in the central region of the pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Physical examination and ultrasound with transabdominal and trans-vaginal probe are commonly used in the surveillance of ovarian cancer patients after initial treatment, since approximately 25-50% of relapses involve the pelvis [32,33,[49][50][51][52][53][54][55]. The SE, SP and DA of ultrasound for recurrent disease range from 45 to 85%, 60 to 100%, and 48 to 87%, respectively [49,[54][55][56] (Table 1).…”
Section: Physical and Ultrasound Examinationmentioning
confidence: 99%
“…Physical examination and ultrasound with transabdominal and trans-vaginal probe are commonly used in the surveillance of ovarian cancer patients after initial treatment, since approximately 25-50% of relapses involve the pelvis [32,33,[49][50][51][52][53][54][55]. The SE, SP and DA of ultrasound for recurrent disease range from 45 to 85%, 60 to 100%, and 48 to 87%, respectively [49,[54][55][56] (Table 1).…”
Section: Physical and Ultrasound Examinationmentioning
confidence: 99%
“…Alternatively, tumor vasculature can be examined and quantified in‐vivo by Doppler ultrasound. Color Doppler ultrasound has been applied to gynecological cancer for detecting recurrence5, predicting prognosis6 and monitoring the response to chemoradiation7. Frequency‐based color Doppler displays the velocity and direction of the signal, while the relatively new technique of power Doppler ultrasound displays the amplitude of the Doppler signal; several independent studies have demonstrated that power Doppler ultrasound is more sensitive than is color Doppler ultrasound in the depiction of tumor vascularity and flow8–10.…”
Section: Introductionmentioning
confidence: 99%
“…Gynecological ultrasound can be used for preoperative diagnosis8–13 and staging14–17 of gynecological cancer. Pelvic recurrences of malignancies can be diagnosed effectively with ultrasound18–22. In the management of patients with subfertility, ultrasound has become pivotal in both diagnosis and treatment23–25.…”
mentioning
confidence: 99%